HUBUNGAN ANTARA BODY IMAGE DENGAN PERILAKU DIET PADA REMAJA KELAS XI IPA 3 DAN 4 SMA N 1 POLANHARJO KLATEN - Sri Yulianti, Tunjung; Indriati, Ratna (Politeknik Insan Husada Surakarta, 2015)
Introduction: body image (body image) to form one's perception of the body, both internally and externally, this perception includes feelings and attitudes aimed at the body that are affected by personal views about the characteristics and the physical ability and the perception of other people's views. Many teens consider themselves overweight or obese easily become so frequent diet in a way that is less true as to limit or reduce the frequency of meals and the number of meals, vomit frequently eaten, so long there is no appetite is very dangerous for teens.Purpose of the study: was to analyze the relationship between body image and dieting behaviors in adolescents Subjects: Population and samples of this study were 60 male and female students in class XI IPA 3 and 4 in SMA Negeri 1 Polanharjo using saturation sampling technique in order to obtain 60 to be the respondent. Method : This research method using cross sectional approach, using a questionnaire with a scale measuring interval. Data were analyzed with Chi-Square. Results: as many as 43 respondents (71.67%) have a positive body image and as many as 59 respondents (98.33%) do a good dietary behavior. There is a significant relationship between body image and dieting behaviors (p = 0.016). Conclusion : There is a relationship between body image and dieting behaviour in adolescents.Keywords: Body image, dieting behaviors, teen